Beyond an anthropocentric view of praxis : towards education for planetary well-being - Heikkinen, Hannu L.T.; Huttunen, Rauno; Mahon, Kathleen; Kemmis, Stephen (Routledge, Taylor & Francis Online, 2026)
A number of philosophical perspectives, such as deep ecology, posthumanism, and new materialisms, to name a few, have challenged the deep-rooted anthropocentric assumptions about human exceptionalism. Yet these non-anthropocentric perspectives must still find a place for human action; they require clear conceptualisations of human action and agency. It is generally acknowledged that human beings have a weighty moral responsibility for correcting the current global ecological crisis. For more than two millennia, theories of praxis supplied conceptualisations of action for the good of humankind. In this paper, we argue that the non-anthropocentric perspectives can be substantially extended and enhanced by a new theory of transformative praxis that breaks through the anthropocentric limit imposed by the notion of ‘the good for humankind’ to embrace collective human action for planetary well-being. We call this approach a praxis orientation to environmental education.